A Comprehensive Literature Review on the Role of Vitamin D in Dry Eye Disease: Implications for Diagnosis and Treatment - Amilia, Annisa (Publikasi Indonesia, 2025)
Dry Eye Disease (DED) is a common ocular disorder characterized by tear film instability, ocular surface inflammation, and visual disturbances that can significantly affect quality of life. Emerging research has highlighted the crucial role of vitamin D in ocular health through its immunomodulatory, anti-inflammatory, and epithelial homeostasis-regulating properties. This comprehensive literature review aims to analyze the role of vitamin D in the pathogenesis, diagnosis, and treatment of DED. A systematic search was conducted in databases such as PubMed, ScienceDirect, and Google Scholar using keywords including “vitamin D,” “dry eye disease,” “ocular surface,” and “tear film stability.” The findings indicate that vitamin D deficiency is strongly associated with an increased risk of DED, exacerbation of inflammatory symptoms, and impaired tear film stability. Clinical studies suggest that vitamin D supplementation may improve both subjective and objective DED symptoms, such as enhanced tear break-up time (TBUT) and reduced Ocular Surface Disease Index (OSDI) scores. However, variations in dosage, treatment duration, and study design remain challenges for establishing standardized therapeutic recommendations. This review emphasizes the need for further large-scale randomized clinical trials to confirm the efficacy and safety of vitamin D supplementation in DED management.